PENGAKUAN AMERIKA SERIKAT TERHADAP PRESIDEN TIDAK SAH DI VENEZUELA DIKAITKAN DENGAN PRINSIP NON-INTERVENSI DALAM PERSPEKTIF HUKUM INTERNASIONAL - Yolanda Pramandika; Zulfikar Jayakusuma; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In International law, recognition is a form of formal statement about the status of a sovereign state from one state to another. Recognition of the new government is an actual problem that often arises. President and Vice President of the United States, Donald Trump and Mike Pence in a tweet on their official state twitter account which contains an official statement announcing officially recognizing Juan Guaido as Provisional President of Venezuela. The United States has also put pressure on Maduro to step down, including imposing an embargo on Venezuela's main oil company and threats of military invasion showing that the United States is at the forefront of the coup.This type of research is a normative juridical research which is classified as research that discusses the principles of law contained in International Law, such as the non-intervention principle. This research when viewed from its character, belongs to approach of legal principles that are descriptive. In normative legal research the data source used is secondary data. Secondary data in this research can be divided into three, namely primary data, secondary data, and tertiary data. Data collection techniques in this research were collected by means of a literature research.From the results of the research found that, first, the United States recognition of the Government supported in Venezuela is a recognition that is not in accordance with the rules of international law. Second, international organization in general and regional have set various rules regarding the forms of intervention and some actions that can mediate disputes between countries. The author advice, that the practice of recognition is expected to be in line with international law, especially the non-intervention principle in order to maintain international peace and security. .Keywords: Non Intervention Principle - Recognition of the New Government